Russian South Gas Corridor Prospects - Khalova, Gul'nar Osmanovna; Pilipenko, Pavel Pavlovich; Isayeva, Elena Andreevna; Petkov, Alexander Emilovich (International Journal of Energy Economics and Policy, 2020)
The European gas market modernization, tied to the adoption of the Third Energy Package in 2009, has led to new challenges and risks for Russian natural gas exporters. The most serious question is the development of an adaptive export strategy, targeted at mutual collaboration and better supply terms. That is especially true for South and South-East Europe (SEE) gas markets, which, due to the new energy policy of Europe, may become a global natural gas transport hub and the key supply region for Russian exporters. It is noted that the European Union countries couldn't reduce the supply of hydrocarbons from the Russian Federation, an example of this is the growth of supplies in 2018. The paper also highlights the role of the countries of SEE in strengthening cooperation and increasing the volume of natural gas supplies from the Russian Federation. Keywords: Energy relations, South and South-East European Countries, Natural Gas Supply JEL Classifications: Q3, Q4 DOI: https://doi.org/10.32479/ijeep.9163